Model Pembelajaran Program Ekstrakurikuler Bahasa Arab dan Implementasinya di Madrasah Aliyah Pesantren - Zulqarnain, Ibnu; Rohman, Muhammad Muti'ur; Maftuhah, Maftuhah; Arifa, Zakiyah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Pesantren based madrasah makes the Arabic language as one of the essential things to be mastered by their students. Madrasah runs several Arabic programs to improve students’ attention and proficiency of Arabic language through extracurricular activities outside the classroom that aim to enrich knowledge and channel students’ interest and talents. However, among these various activities, many of it do not operate well because of lack of skills. The purpose of this study is to describe the implementation of extracurricular programs in MA Pesantren Nurul Ulum and the language learning models used. The research used the descriptive qualitative method. The data sources of this research are the instructors in the Arabic extracurricular program, the location, files and photos of activities that carried out by interview, observation, and documentation. The results of this study are the implementation of extracurricular programs in MA Pesantren Nurul Ulum by using various language learning models following the objectives of the activities; cooperative models in Arabic Olympics extracurricular, Taqdimul Qishshah, and Khithabah, communicative-eclectic and quantum models in quiz extracurricular. Diverse learning models make the learning process more varied for teachers and students while train student competencies. Then it should be realized as a whole in Arabic language education.